Customer engagement mediates the effect of content marketing on customer retention among mie sedaap consumers in surabaya - Hasyim, Alwi Fu'ad; Winarno, Sri Tjondro; Wijayati, Prasmita Dian (Manajemen dan Bisnis, 2025)
The transformation to digital marketing has significantly changed the competitive landscape of Indonesia's instant noodle industry. New brands have gained traction through effective content marketing (CM), challenging Mie Sedaap to adapt in order to retain its customers. This study aims to examine how CM influences customer retention (CR), with customer engagement (CE) as a mediating variable. Utilizing WarpPLS 8.0 and the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, primary data was gathered using purposive sampling. A total of 130 respondents completed the questionnaire. Four hypotheses were tested to explore both direct and mediating effects. All hypotheses were supported, confirming significant relationships among the variables. The findings reveal that CM positively impacts CR, both directly and indirectly through CE. Customers who engage by liking, commenting, or sharing branded content are more emotionally connected to the brand, enhancing loyalty, repeat purchases, and word-of-mouth promotion. These results underscore the strategic importance of engaging and emotionally resonant content in fostering long-term customer relationships. For companies in the fast-moving consumer goods (FMCG) sector, particularly instant noodles, crafting interactive, relevant, and emotionally appealing content is critical. Investing in such strategies can strengthen customer loyalty and provide a competitive edge in the increasingly digital marketplace.